Pengaruh Waktu Perendaman Terhadap Uji Kuat Tekan Paving Block Menggunakan Campuran Tanah dan Kapur dengan Alat Pemadat Modifikasi - ANDANDANINGRUM, DELLA; Iswan, Iswan; Setyanto, Setyanto (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2016)
Paving block is a composition ingredient construction made from mixture of portland cement or a kind of adhesive hydrolysis, water, and aggregates with or without other ingredients. Concrete bricks can colored as original color or given substance color on composition and used for page both inside nor outside construction. In this study the process of manufacture of paving blocks will use a mix of soil and chalk. Moreover, soaking of the paving blocks that are expected to increase the strength of paving blocks is according to SNI 03-0691-1996. Soil samples tested were from Kota Baru, South Lampung. Composition blend of soil and chalk with variation time to soak is 7 days, 14 days, 21 days, and 28 days, as well as to the treatment of pre-combustion and post-combustion of the sample of paving blocks. Based on the results of physical testing the original soil, USCS classify soil samples as fine-grained soil and belong to the group ML. Results from this study is the manufacture of paving blocks using silt soil and chalk soil material that does not meet the specifications of SNI 03-0691-1996. This is because the weakness on modification compactor which are use when make a sampel. For the compressive strength of paving blocks pre-combustion and post-combustion are best shown in soaking time of 28 days. The compressive strength that generated as a whole still does not meet the specifications of the paving block SK SNI 03-0691-1996 that is a minimum compressive strength at 85 kg/cm2. But value of water absorption meets the specification 03-0691-1996 which is 3%-10%.Keyword : Paving block, slit soil, compressive strength, soil burning.